A novel multifunctional glycidylamine epoxy resin containing phthalide cardo structure: Synthesis, curing kinetics and dynamic mechanical analysis. (August 2019) - Xiong, Xuhai; Guo, Xichao; Ren, Rong; Zhou, Lu; Chen, Ping
Abstract: A novel glycidylamine epoxy resin containing phthalide cardo structure (TGMP) was designed and synthesized based on o -cresolphthalein using a three-step procedure. Its curing systems were prepared using methyl-nadilic anhydride (MNA) and 2-ethyl-4-methylimidazole (EMI-24) as the curing agent and accelerating agent, respectively. The chemical structures of synthetic intermediate, epoxy resin and its curing systems were characterized by Fourier transform infrared (FTIR) spectra and nuclear magnetic resonance (NMR) spectra. The curing behavior and kinetics were investigated by differential scanning calorimetry (DSC) and the activation energies were calculated according to the Kissinger equation and Flynn-Wall-Ozawa (FWO) equation. The TGMP/MNA/EMI-24 system is of more reactivity more that of pure TGMP. The Friedman method was used to describe the progress of the curing reaction of the TGMP/MNA/EMI-24 system, finding it follows the autocatalytic reaction model and n th-order reaction mechanism is predominant. The thermal-mechanical properties of the TGMP/MNA/EMI-24 composites were studied by dynamic mechanical analysis (DMA). The tan δ curves show double peaks and the maximum glass transition temperature is up to 345 °C. Highlights: Synthesis of a multifunctional phthalide-containing glycidylamine epoxy resin (TGMP). The homopolymerization activation energy of the pure TGMP resin equals to 114.23 kJ/mol. The curing activation energy of TGMP/MNA/EMI-24 system equals to 57.64 kJ/mol. The TGMP/MNA/EMI-24 curing reaction follows the autocatalytic mechanism. T g of TGMP/MNA/EMI-24 cured product is above 345 °C.